(3JWHjbGJ aj GdUfGYI hGdJYdjes - (3ShSf TGcQ(B, (3eLjOs; (3GdRjGOGJ(B, (3eMeO YhGOs ((3YeGf(B:s (3OGQ GdUaGA(B,s, 2007)
(3eaGgje heUWdMGJ aj GdLhOI, Gdeaghe GdGSdGej ddLhOI, feGPL GOGQI GdLhOI GdTGedI, eJWdHGJ JWHjb GOGQI GdLhOI GdTGedI hfeGPL aj GdJWHjb, GbJUGOjGJ GdLhOI hJcGdjagG, CSGdjH GdVHW GdGMUGFj ddLhOI, LhGFR GdLhOI, GdLhOI GdTGedI hGdGjRh, GdLhOI GdTGedI hGdJZjjQ, GOGQI GdLhOI GdTGedI aj GdeDSSGJ GdJQHhjI, eShZGJ hCgOGa heHGOF heJWdHGJ JWHjb GdLhOI GdTGedI aj GdJYdje GdYGdj, eYGjjQ GdLhOI GdTGedI aj GdLeGYGJ, GOGQI GdLhOI GdTGedI aj GdJYdje GdLGeYj, GSGdjH GdLhOI hGdGYJeGO aj Jbhje GOGA GdeDSSGJ GdJQHhjI hGdLGeYjI, feGPL JWHjb GdLhOI GdTGedI aj GdeDSSGJ GdJQHhjI hGdLGeYjIs
Keywords: (3GOGQI GdGYeGds; (3GdJYdjes; (3VHW GdLhOIs